The predictive role of L2 learners’ resilience in language classroom engagement - Alahmari, Arwa; Alrabai, Fakieh (Frontiers in Education, 2024)
The present study explores the relationship between the concepts of foreign language (L2) learners’ resilience and their behavioral, emotional, cognitive, and agentic engagement. It also aims to understand the role of L2 resilience in students’ overall engagement. The study employs a quantitative approach and utilizes online questionnaires by which it collected data from 123 English as a foreign language (EFL) university students. Data analysis procedures involved descriptive statistics, correlation analysis to identify the levels of L2 resilience and engagement among the EFL participants as well as the associations between these constructs; and a multiple regression analysis to unveil the explanatory power of learner resilience in language engagement. The findings revealed moderate levels of L2 resilience and overall engagement as well as significant correlations between learners’ resilience and their overall engagement and its four dimensions. The linear multiple regression analysis showed that EFL learners’ resilience has explained around a third (30%) of the total variance in their overall engagement. These findings provide insights into the importance of EFL learners’ resilience in accounting for their engagement. Such findings highlight the significance of promoting learners’ resilience for the purpose of enhancing their L2 engagement and thereby leading a successful language learning journey.